Clinical role of intraperitoneal chemotherapy in patients with pancreatic ductal adenocarcinoma concomitant with occult peritoneal dissemination: A multicenter retrospective study - Tomohisa Yamamoto; Toshio Shimokawa; Masamichi Hayashi; Masamichi Mizuma; Katsuhisa Hirano; Atsushi Oba; Toshimichi Asano; Hideyo Miyato; Makoto Yoshida; Ippei Matsumoto; Yasunari Kawabata; Katsunori Sakamoto; et al. (Annals of Gastroenterological Surgery)
Abstract Background The effectiveness of intraperitoneal chemotherapy using paclitaxel (i.p.‐PTX) in pancreatic ductal adenocarcinoma (PDAC) patients with peritoneal dissemination remains elusive. The aim of this study is to investigate the clinical outcome of patients treated with i.p.‐PTX combined with systemic chemotherapy compared with current standard chemotherapy including gemcitabine plus nab‐paclitaxel and FOLFIRINOX. Methods Data of patients with peritoneal dissemination was retrospectively collected and analyzed (i.p.‐PTX, n = 83; control, n = 86). Inverse probability of treatment‐weighted analyses (IPTW) was used to balance baseline characteristics between two groups. Survival curves were estimated using Kaplan–Meier method, and the differences were compared using the log‐rank test. Results No significant differences were noted in overall survival (14.9 vs. 15.5 months, p = 0.481) and progression free survival (9.5 vs. 9.1 months, p = 0.267) between i.p.‐PTX and the control groups. Nevertheless, i.p.‐PTX (9.9 months) significantly prolonged the median progression‐free survival (PFS) time compared with the control (8.6 months), among the matched patients using IPTW (hazard ratio 0.666, p = 0.041). Moreover, subgroup analysis among the patients whose primary tumor were evaluated either as resectable or borderline resectable disease revealed significantly better overall survival in the i.p.‐PTX group compared with the control group (21.3 vs. 14.7 months, hazard ratio; 0.532, p = 0.033). Conversion surgery was more frequently performed in the i.p.‐PTX group than the control group (24% vs. 4%, p = 0.006). Conclusion The i.p. PTX regimen prolonged PFS but not overall survival, and subgroup analysis suggested the possibility of survival benefit in patients with occult peritoneal dissemination whose primary tumor was classified as resectable/borderline resectable disease.